(untitled) (Research Nepal Journal of Development Studies, 2019)
The historical Analysis of Baudha Stupa and Kassap Buddha is the study of the history of Baudha stupa of Baudha Kathmandu Nepal. The main objective of the study is to analyze the historical importance of Boudhanath Stupa and Kasyap Buddha. Comparative Historical Analysis (CHA) method has been applied to analyze the collected facts and information. The story of Nalanika (Nalanika Jatak Katha) claims that Shringa (Having a horn in head) sage was the grandson of Kassap and son of Vibhandak sages was born in Mahalaxmi municipality, Lankuri Bhanjyang Shringa Rishi Ashram. Therefore, Kassap Buddha had visited and settled few times in the municipality. Thus Baudha Stupa – made by relics of Kassap Budha- Baudha Kathmandu has clear relation with Shringa Rishi Ashram of Lalitpur.